Entre Argentina e Italia pasando por Yugoslavia - Regazzoni, Susanna (Ars et humanitas, 2017)
Crossing the River by Bicycle (Cruzando el río en bicicleta) is a text that can be defined as self-fiction, that is, a story that is halfway between narrative and biography and that presents the memories of a woman's childhood and adolescence that take place between Belgrade, Buenos Aires and Trieste. Her experiences thus occur in three countries and three different languages over a timeframe years that goes from the Argentine military dictatorship to the tragedy of the wars in the former Yugoslavia. It is a novel that refers to the identity of Argentina, a country constituted by the contribution of European immigrants from the late nineteenth century to the midtwentieth century - in this case the Istrian family of the author - and marked by the exile of the many young people who travelled abroad during the dictatorships of the second half of the twentieth century. The first edition was published in Spanish, and has been translated into Italian by the same author with a different ending.
Keywords: argentinska književnost; avtofikcija; identiteta; literarne študije; Prenz Kopušar, Ana Cecilia; spomini